Complication rates of resident‐performed cataract surgery: Impact of early introduction of cataract surgery training. Issue 9 (September 2018) - Ellis, Erika M.; Lee, Jeffrey E.; Saunders, Luke; Haw, Weldon W.; Granet, David B.; Heichel, Chris W.
Abstract : Purpose : To determine the effect of the early introduction of cataract surgery training on the complication rates of resident‐performed cataract surgery. Setting : University of California San Diego, San Diego, California, USA. Design : Retrospective case series. Methods : Two classes of ophthalmology residents were examined, one class with a late introduction of cataract surgery and one with an early introduction of cataract surgery. All cataract cases in which residents acted as primary surgeon were included. Patient charts were reviewed to collect data on patient characteristics, surgical details, and intraoperative and postoperative complications. Results : The late‐introduction cohort comprised 3 residents who performed 540 cataract cases, all during their final year of residency. The early‐introduction cohort comprised 4 residents who performed 780 cataract cases beginning in the first year of residency. The late‐introduction cohort had higher rates of major intraoperative complications than the early‐introduction cohort (8.5% versus 3.1%) and of anterior vitrectomy (7.6% versus 2.1%) (both P < .001). Examination of the anterior vitrectomy rate as a function of experience showed the early‐introduction cohort had a stable anterior vitrectomy rate of 1% to 2% throughout training, while the late‐introduction cohort had a peak anterior vitrectomy rate of 12% at approximately case 20. Multivariable regression analysis showed the early‐introduction cohort was independently associated with a lower rate of anterior vitrectomy (hazard ratio, 0.49; 95% confidence interval, 0.36‐0.66) after adjusting for differences in patient characteristics and surgical complexity. Conclusions : Early introduction of cataract surgery training significantly decreased the rate of major intraoperative complications, specifically anterior vitrectomy, in resident‐performed cataract surgeries.